Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen